Role of Social Media in Managing Everyday Information: A Case Study of Urban Teens in Pakistan - Saima Hanif; Nosheen Fatima Warraich (JOURNAL OF MEDIA & COMMUNICATION, 2023)
This study attempts to fill the research gap that exists in the management of everyday information. It seeks to explore if and how urban teenagers manage everyday information with the help of social media. A qualitative study was conducted and Sample was 25 Pakistani urban teenagers aged 13 – 19. The sample was chosen, as Generation Z individuals were targeted in this study. Face-to-face interviews were conducted, however, due to Covid-19 pandemic outbreak, few interviews were obtained via the software “Zoom”. Thematic analysis was done using the software NVivo. It was concluded that managing information forms a critical part of everyday information practices of urban teenagers, especially after the advent of online classes after which every teenager has access to social media and digital gadgets of their own. Urban teenagers manage information by using all social media platforms and also sharing it with their peers and family through digital media. They are managing their information to handle the information overload and to manage, organize and summarize the collected information for their future use and quality management. This practice is also developing their relationships, identifies the cultural differences, and makes them realize what and how to manage. Based on the general analysis and suggestions, opinions have been created to further improve these practices. This study may be replicated on rural teens to know their information managing practices.